Clinical effect of chlorhexidine and sodium fluoride on corrosion behavior and surface topography of nitinol orthodontic archwires - Osama Gamil Abd El Gawad Farrag; Nabeel El-Desouky Abou Shamaa; Walaa Elsayed Elgameay; Dalia A. Bayoumi (BMC, 2024)
Abstract Background Alterations in the mechanical properties of the materials utilized in orthodontic appliances could affect the working properties of the appliances, thereby affecting clinical progress and outcome. Numerous studies have confirmed the correlation between alloy corrosion and raised surface roughness, which has a direct impact on the working characteristics of orthodontic archwires. Methods Thirty nickel-titanium (NiTi) orthodontic archwires were utilized in this study. Patients were randomly selected and allocated into three groups according to the randomization plan; (The control group): subjects practiced regular oral hygiene; (The fluoride group): subjects used fluoride for intensive prophylaxis; (The chlorhexidine group): subjects used chlorhexidine. Representative samples were evaluated by SEM, and then SEM images with high resolution were examined using Image J software to determine the surface roughness and obtain the results for further statistical analysis. Results Our findings indicated a significant difference was found between the three groups regarding the anterior and posterior parts between the control and the two other groups and a non-significant difference between NaF and CHX groups. Overall, the p-value for group comparisons was 0.000 for both parts, indicating a highly significant difference especially between the control and NaF groups. Conclusion Mouthwashes containing sodium fluoride demonstrated more significant surface alterations than the control and CHX groups and should be prescribed in accordance with orthodontic materials to reduce side effects.